Perceptions on the Selection of Seed Varieties for Paddy Farming in Palakkad: A Qualitative Inquiry - Sabu, P J; Pulikkottil, Minju David; Roy, Deepa (Indian Journal of Extension Education, 2025)
Paddy is an important item of food and a source of livelihood in Palakkad district of Kerala. However, it was observed that the productivity of paddy cultivation has been declining in Palakkad. Earlier research has identified some of the causes of the decline in the productivity of paddy. But the decision on the selection of seed varieties of paddy remains under-investigated in a qualitative manner. Considering this context, the present research attempted to analyse the selection-decision of seed varieties of paddy in Palakkad. To meet this goal, the present research has used a qualitative approach. The primary information was collected through in-depth interviews and focus group discussions with respondents in 2025. These responses were analysed by word-cloud analytics. Based on the analysis, it was found that farmers used the traditional seed varieties of paddy in the ‘dry season’ and hybrid varieties in the ‘wet season’. The major factors that influenced their seed selection were climate conditions, satisfaction from farming, size of the holding, availability of irrigation facilities, input costs, yield capacity, market for paddy and nature of Government support. Based on these findings, the present research argues that novel paddy varieties of seeds should be developed to suit the region-specific climate and socio economic conditions of paddy farmers in Palakkad.
Keywords: Paddy cultivation; Seed varieties; Traditional seeds; Hybrid seeds